Step
*
1
of Lemma
eo-forward-forward
.....assertion..... 
1. Info : Type
2. eo : EO+(Info)
3. e1 : E
4. e2 : E
5. e1 ≤loc e2 
⊢ (λe.(((eo."dom" e) ∧b (e1 ≤loc e ∨b(¬bloc(e) = loc(e1)))) ∧b (e2 ≤loc e ∨b(¬bloc(e) = loc(e2)))))
= (λe.((eo."dom" e) ∧b (e2 ≤loc e ∨b(¬bloc(e) = loc(e2)))))
∈ (es-base-E(eo) ─→ 𝔹)
BY
{ (Fold `es-dom` 0 THEN Ext THEN Reduce 0)⋅ }
1
1. Info : Type
2. eo : EO+(Info)
3. e1 : E
4. e2 : E
5. e1 ≤loc e2 
6. x : es-base-E(eo)
⊢ ((es-dom(eo) x) ∧b (e1 ≤loc x ∨b(¬bloc(x) = loc(e1)))) ∧b (e2 ≤loc x ∨b(¬bloc(x) = loc(e2))) 
= (es-dom(eo) x) ∧b (e2 ≤loc x ∨b(¬bloc(x) = loc(e2)))
2
.....wf..... 
1. Info : Type
2. eo : EO+(Info)
3. e1 : E
4. e2 : E
5. e1 ≤loc e2 
⊢ es-base-E(eo) = es-base-E(eo) ∈ Type
Latex:
.....assertion..... 
1.  Info  :  Type
2.  eo  :  EO+(Info)
3.  e1  :  E
4.  e2  :  E
5.  e1  \mleq{}loc  e2 
\mvdash{}  (\mlambda{}e.(((eo."dom"  e)  \mwedge{}\msubb{}  (e1  \mleq{}loc  e  \mvee{}\msubb{}(\mneg{}\msubb{}loc(e)  =  loc(e1))))  \mwedge{}\msubb{}  (e2  \mleq{}loc  e  \mvee{}\msubb{}(\mneg{}\msubb{}loc(e)  =  loc(e2)))))
=  (\mlambda{}e.((eo."dom"  e)  \mwedge{}\msubb{}  (e2  \mleq{}loc  e  \mvee{}\msubb{}(\mneg{}\msubb{}loc(e)  =  loc(e2)))))
By
(Fold  `es-dom`  0  THEN  Ext  THEN  Reduce  0)\mcdot{}
Home
Index